2019
DOI: 10.1001/jamapsychiatry.2018.3907
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hydroxylmethyl Glutaryl Coenzyme A Reductase Inhibitors, L-Type Calcium Channel Antagonists, and Biguanides With Rates of Psychiatric Hospitalization and Self-Harm in Individuals With Serious Mental Illness

Abstract: Key Points Question Are drugs in common use for physical health problems (hydroxylmethyl glutaryl coenzyme A reductase inhibitors, L-type calcium channel antagonists, and biguanides) associated with reduced rates of psychiatric hospitalization and self-harm in individuals with serious mental illness? Findings In this series of within-individual cohort studies of 142 691 patients with bipolar disorder, schizophrenia, or nonaffective psychosis, exposure to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…Some data suggest that, amongst AHT classes, calcium channel blockers (CCBs) and renin-angiotensin system (RAS) agents (angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II inhibitors (ARBs)) are more protective in this regard than are diuretics and beta-blockers ( Marpillat et al, 2013 ; Mukete et al, 2015 ; Mullapudi et al, 2016 ; Rouch et al, 2015 ; Zhuang et al, 2016 ). Less extensive data also report associations between CCB and RAS agent use with functional psychiatric disorders such as psychosis ( Hayes et al, 2019 ) and depression ( Boal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some data suggest that, amongst AHT classes, calcium channel blockers (CCBs) and renin-angiotensin system (RAS) agents (angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II inhibitors (ARBs)) are more protective in this regard than are diuretics and beta-blockers ( Marpillat et al, 2013 ; Mukete et al, 2015 ; Mullapudi et al, 2016 ; Rouch et al, 2015 ; Zhuang et al, 2016 ). Less extensive data also report associations between CCB and RAS agent use with functional psychiatric disorders such as psychosis ( Hayes et al, 2019 ) and depression ( Boal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adjunct Therapy for Schizophrenia, Bipolar Disorder, and Non-Affective Psychosis [128] Mechanism of Action (MOA) was referenced from Drug Bank (https://www.drugbank.ca/). Original and repurposed indications were referenced from the cited study.…”
Section: Cardiac Arrythmias Angina Hypertensionmentioning
confidence: 99%
“…The extensive cardiovascular prescribing of CCBs allows for pharmacoepidemiological studies to assess whether their use is associated with an altered risk or course of neuropsychiatric disorders. Hayes et al 17 recently showed that, among patients with psychosis, rates of psychiatric admission and self-harm were 10–20% lower during periods of CCB treatment. The design rules out confounding by indication and no similar benefits were seen for thiazide diuretics or for non-psychiatric admissions, suggesting a degree of specificity.…”
Section: Recent Vgcc and Ccb Developmentsmentioning
confidence: 99%